Staged reconstruction for humeral osteomyelitis after severe crush injury of the shoulder: a case report - Kow, Ren Yi; Nazri, Mohd Yusof; Abas, Muhammad Firdaus; Low, CL (Malaysian Orthopaedic Association, 2022)
The incidence of humeral osteomyelitis is relatively rare as compared to incidence of lower limb osteomyelitis. Despite having no guideline in the management of humeral osteomyelitis, surgeons have utilised their experience in managing lower limb osteomyelitis to treat humeral osteomyelitis. By adhering to principles including thorough debridement of necrotic bone and soft tissue, staged bony and/or soft tissue reconstruction, and targeted antimicrobial therapy, a good outcome can be achieved in the management of humeral osteomyelitis. We report a case of Cierny-Mader type IV proximal humeral osteomyelitis after a severe crush injury of the left shoulder and its subsequent two-stage reconstruction using internal fixation and pedicled Latissimus dorsi musculocutaneous flap.